SPEIR: developing a common information environment in Scotland. - Nicholson D; Dunsire G; Macgregor G (Electronic Library, 2006)
Purpose-To report on the work of the SPEIR project and indicate its relevance beyond the Scottish information environment. SPEIR was funded by the Scottish Library and Information Council to identify, research, and develop the elements of an internationally interoperable Scottish Common Information Environment (SCIE) for Library, Museum and Archive domain information services, and to determine the best path for future progress. A key focus was to determine the distributed information infrastructure requirements of a pilot Scottish Cultural Portal being developed in parallel with the SPEIR work, building on existing pilot initiatives such as the CAIRNS distributed catalogue and landscaper, the SCONE collections database, the SCAMP staff portal and an embryonic organisational infrastructure based on the Confederation of Scottish Mini-cooperatives (CoSMiC).Design/methodology/approach-A series of practical pilots was undertaken. These were underpinned by relevant desk and field research and conducted within an overarching holistic approach to developing the distributed environment.Practical implications-Key outcomes included the creation of a single upgraded integrated service incorporating an extended distributed catalogue, collections database, and landscaper, the creation of a pilot distributed digital library, the development of open-URL-based facilities to permit portals to incorporate 'canned searches' of the catalogue, the collections database, the SDDL, and other compatible services, an illustrative pilot Scottish terminology mapping service, and various organisational infrastructure and professional support improvements.Originality/value-The embryonic technical and organisational infrastructure reported may provide a model for other small countries (or regions within larger countries) seeking a coherent approach to the development of an interoperable information environment.